2015
DOI: 10.1007/s11249-015-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet Thickness on Wear of Graphene–Polytetrafluoroethylene (PTFE) Composites

Abstract: Under conditions of dry sliding against polished stainless steel, the steady-state wear rates of composites of polytetrafluoroethylene (PTFE) filled with graphene platelets with typical platelet thickness varying between 1.25 and 60 nm were measured. The fraction of the graphene platelets was varied between 0.02 and 30 wt%, also including 0 % unfilled PTFE. With 4 % loading of the 1.25 and 1.6 nm thick graphene platelets, the measured steady-state wear rates approached *4 9 10 -7 mm 3 /Nm levels which are roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…3 Several works in the literature have assessed the influence of graphene fillers on the tribological and mechanical properties of different polymers, such as polyacrylonitrile [15], poly(vinyl chloride) [16], polyimide [17], polytetrafluorethylene (PTFE) [18] and ultrahigh molecular weight polyethylene [19]. However, only a few works have appeared about graphene/PEEK composites [20][21][22][23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 Several works in the literature have assessed the influence of graphene fillers on the tribological and mechanical properties of different polymers, such as polyacrylonitrile [15], poly(vinyl chloride) [16], polyimide [17], polytetrafluorethylene (PTFE) [18] and ultrahigh molecular weight polyethylene [19]. However, only a few works have appeared about graphene/PEEK composites [20][21][22][23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, incorporation of alumina [6], serpentine [7] nanoparticles enhanced the wear resistance and even ensured ultralow wear performance of PTFE. Trials were made also to improve the wear performance of PTFE by using carbonaceous nanofillers such as carbon nanotube (CNT) [8] and graphene [9][10]. Graphene and its derivatives proved to be very attractive self-lubricating materials themselves to achieve low friction and low wear rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…showed that expanded graphite combined with other nanofillers give a synergistic effect to improve the mechanical properties of PTFE composites. However, there exists limited information regarding PTFE composites filled with graphene nanoplatelets and how it influences the physical properties of the PTFE . Furthermore, the proper fabrication methods of these nanocomposites are also relatively unestablished and very few articles address the preparation of nanofilled‐PTFE composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists limited information regarding PTFE composites filled with graphene nanoplatelets and how it influences the physical properties of the PTFE. 5,7,9,10 Furthermore, the proper fabrication methods of these nanocomposites are also relatively unestablished and very few articles address the preparation of nanofilled-PTFE composites. Most of the guidelines are provided by the manufacturers recommending the correct processing conditions regarding preform pressures and the sintering cycles for filled and unfilled PTFE.…”
Section: Introductionmentioning
confidence: 99%